Clinical Outcomes of MRI-Guided Adaptive Brachytherapy for Each Fraction in Locally Advanced Cervical Cancer: A Single Institution Experience - Chi, Yunbo; Pan, Ying; Zhang, Ning; Han, Dongmei; Guo, Xin; Mao, Zhuang; Cheng, Guanghui (Frontiers in Oncology, 2022)
Purpose: To evaluate clinical outcomes of MRI-guided adaptive brachytherapy (MR-IGABT) for each brachytherapy fraction in patients with locally advanced cervical cancer (LACC). Methods and Materials: A retrospective analysis was performed on 97 consecutive patients with LACC treated with 44.0-50.4 Gy external beam radiotherapy (EBRT) +/- concurrent platinum-containing chemotherapy followed by 4×7 Gy MR-IGABT between September 2014 and April 2019. Intracavitary (IC)/interstitial (IS)/hybrid intracavitary and interstitial (IC/IS) brachytherapy was used in MR-IGABT. Brachytherapy planning and dose reporting followed the GEC-ESTRO recommendations. Clinical outcomes including overall survival (OS), cancer specific survival (CSS), progression free survival (PFS), local control (LC) and treatment related toxicity evaluated by the RTOG criteria were analysed. Kaplan-Meier and univariable and multivariable Cox regression analysis were used to analyse the prognostic factor. Results: Median follow-up was 21.1 months. Median dose to 90% (D90) of the high-risk clinical target volume (HR-CTV) was 91.7 Gy (range 76.7~107.2 Gy). Two-year OS, CSS, PFS, LC were 83.5%, 84.1%, 71.1%, 94.8%, respectively. Four patients (4.1%) suffered from Grade 3 late gastrointestinal radiation toxicity, and no other Grade 3 or greater radiation toxicity occurred. Initial HR-CTV was an independent factor of OS (P=0.001, HR=1.018 per cm3), PFS (P=0.012, HR=1.012 per cm3), and LC (P=0.011, HR=1.028 per cm3). The HR-CTV D90 (P=0.044, HR=0.923 per Gy) was an independent factor of PFS. Age was an independent factor of LC (P=0.010, HR=1.111 per year). Conclusion: For patients with LACC, MR-IGABT was effective and safe. It showed favourable LC, OS, and minimal toxicity. Moreover, initial HR-CTV, HR-CTV D90 and age were significant prognostic factors.